Correction: Pickering nano-emulsions stabilized by solid lipid nanoparticles as a temperature sensitive drug delivery system. Issue 42 (21st October 2019) - Dieng, Sidy Mouhamed; Anton, Nicolas; Bouriat, Patrick; Thioune, Oumar; Sy, Papa Mady; Messaddeq, Nadia; Ennahar, Said; Diarra, Mounibé; Vandamme, Thierry
Abstract : Correction for 'Pickering nano-emulsions stabilized by solid lipid nanoparticles as a temperature sensitive drug delivery system' by Sidy Mouhamed Dieng et al., Soft Matter, 2019, DOI: ; 10.1039/c9sm01283d .